Calcium‐activated nucleotidase 1 silencing inhibits proliferation, migration, and invasion in human clear cell renal cell carcinoma. Issue 12 (17th May 2019) - Liu, Xin; Yang, Zhenxing; Luo, Xing; Luo, Jing; Fu, Weihua; Fang, Zhenqiang; Xia, Ding; Li, Longkun; Xu, Jie
Abstract: Calcium‐activated nucleotidase 1 (CANT1, belongs to the apyrase family, is widely expressed in various organs. However, the biological function of CANT1 remains poorly explored. In this study, we aimed to investigate the expression profile and functions of CANT1 in clear cell renal cell carcinoma (ccRCC). Our data show that the protein level of CANT1 was significantly higher in tumor tissues than in adjacent normal tissues. CANT1 silencing suppressed cell proliferation, migration, and invasion obviously in 769‐P and 786‐O cells, arrested cell cycle in S phase and promoted apoptosis in 769‐P cells. In conclusion, the present study shows the different expression mode of CANT1 in human ccRCC tumor tissue and adjacent normal tissue, denotes the function of CANT1 in ccRCC cells and provides potential molecular mechanisms and pathways of CANT1 antitumor function in ccRCC. Abstract : Our study shows that protein level of calcium‐activated nucleotidase 1 (CANT1) is upregulated during the tumorigenesis of human clear cell renal cell carcinoma (ccRCC), demonstrates knockdown of CANT1 expression can inhibit cell proliferation, migration, and invasion in human ccRCC, cell‐cycle arrest in the S phase and promote cell apoptosis.